The emerging landscape of novel 4-1BB (CD137) agonistic drugs for cancer immunotherapy - Christina Claus; Claudia Ferrara-Koller; Christian Klein (mAbs)
The clinical development of 4–1BB agonists for cancer immunotherapy has raised substantial interest during the past decade. The first generation of 4–1BB agonistic antibodies entering the clinic, urelumab (BMS-663513) and utomilumab (PF-05082566), failed due to (liver) toxicity or lack of efficacy, respectively. The two antibodies display differences in the affinity and the 4–1BB receptor epitope recognition, as well as the isotype, which determines the Fc-gamma-receptor (FcγR) crosslinking activity. Based on this experience a very diverse landscape of second-generation 4–1BB agonists addressing the liabilities of first-generation agonists has recently been developed, with many entering clinical Phase 1 and 2 studies. This review provides an overview focusing on differences and their scientific rationale, as well as challenges foreseen during the clinical development of these molecules.